Compression moduli of foamed films of fluorinated ethylene propylene copolymers determined by nanoindentation - Zirkel, Larissa; Maier, Verena; Durst, Karsten; Münstedt, Helmut (Polymer Testing, 2011)
Nanoindentation was applied to determine the elastic moduli in the compression mode of films of fluorinated ethylene propylene copolymers (FEP) foamed by means of supercritical carbon dioxide. For this purpose, a flat punch indenter with a diameter larger than the average cell size of the foams was found to be appropriate. The dependence of the mechanical properties of the films on their cellular structure was investigated by varying material and process parameters: molar mass of the FEP, the magnitude of the pressure drop and the temperature during the foaming process. The elastic modulus showed a strong influence of the cellular structure of the films. A decrease of the molar mass of FEP as well as an increase of pressure drop and foaming temperature considerably reduced the elastic modulus of the foams generated. This lowering of the stiffness correlated with the decrease of foam density. In addition, a significant contribution of the cellular morphology and the thickness of the compact skin layers of the foams could be noted. A further reduction of the foam stiffness was achieved by a biaxial stretching of the foams, which deformed the cells into a lens shape.
WW1::864